De volta para o afrofuturo: um olhar sociológico sobre representações do afrofuturismo no Brasil - Lima, Cairo Henrique dos Santos (2024)
This master's thesis aims to study Afrofuturism in Brazil, emphasizing the articulation of the Afrofuturist aesthetic project through different artistic languages. Our general objective is to characterize the relationships between Afrofuturism in Brazil and the African diaspora, discussing multiple forms of representation. To this end, we seek to think sociologically about the creative relationships that exist between the historical context of Afrofuturism, cultural representations and the social experiences of Afrofuturist artists. The specific objectives are: a) to understand the influence of cultural hybridization on the representations and experiences of Afrofuturism in Brazil; b) verify, in Afrofuturist works, the meanings of common aesthetic elements, such as body, territory and State; c) characterize the experiences of Afrofuturist artists in Brazil. The following text presents a possible genealogy of Afrofuturism in the United States, a sociological interpretation regarding the reinterpretation of the aesthetic antecedents of Afrofuturism in Brazil, a discussion of its conceptual assumptions, a set of indepth analyzes of Brazilian Afrofuturist works, and interviews with brazilian afrofuturists artists. Our methodological framework is based on content analysis with an emphasis on the theory of cultural representation applied to works from different artistic niches, and in-depth interviews with the artist-subjects. Starting from the theoretical perspective of Cultural and Post-Colonial studies, we seek to discuss processes of hybridization based on themes such as creative black agency and criticism of modern thought.